Outcomes and Complications of Open vs Minimally Invasive Surgical Repair of Acute Achilles Tendon Rupture: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. Issue 1 (January 2022) - Attia, Ahmed K.; Khamis, Karim Mahmoud; Dhooghe, Pieter; Bariteau, Jason T.; Labib, Sameh A.; Myerson, Mark S.
Category: Ankle; Sports; Trauma Introduction/Purpose: Traditionally, open surgical repair has provided improved functional outcomes, reduced re-rupture rates, and quicker recovery and return to activities at the expense of increased wound complications of infection and skin necrosis compared to nonoperative management. Ma and Griffith in 1977 introduced the percutaneous approach, and over the following decades, multiple improved techniques, and modifications thereof, have been described with comparable outcomes to the open repair. The current study aims to provide updated level I evidence comparing the open and minimally invasive (MIS) through a comprehensive search of literature published in English, Spanish, Portuguese, and German while avoiding limitations of previous studies such as heterogeneous study designs and a small number of included studies. Methods: Following the PRISMA guidelines, two independent team members searched several databases to identify randomized controlled trials (RCTs) comparing open and MIS Achilles tendon repairs. The primary outcomes were (1) Sural nerve injury, (2) Skin complications, (3) Infection (deep/superficial), whereas the secondary outcomes were (1) AOFAS/ATRS score, (2) surgical time, (3) re-rupture (4) adhesions (5) ankle range of motion. Population: Achilles tendon rupture Intervention: MIS repair Control: Open repair Outcomes: Primary: (1) Sural nerve injury, (2) Skin complications, (3) Infection (deep/superficial) Secondary: (1) AOFAS/ATRS score, (2) surgical time, (3) re-rupture, (4) adhesions, (5) ankle range of motion (6) other complications. Results: Ten RCTs qualified for the meta-analysis with a total of 522 patients. 260(49.8%) patients had open repair while 262(50.2%) had MIS repair. The mean total complication rate was 15.5% (0-36.4%) in open repair vs. 10.4% (0-45.5%) in MIS repair, with non-significant statistical difference (RR= 1.50, CI=0.87-2.57, p= 0.14;I2=40%). The mean re-rupture rate was 2.5% (0-6.8%) in open repair vs. 1.53% (0-4.6%) with MIS repair, with non-significant statistical difference (RR=1.56, CI=0.42-5.70, p= 0.50;I2=0%). No cases of sural nerve injury were reported in the open repair group. The mean sural nerve injury was 3.4%(0-7.3%) in the MIS group, that was statistically significant (RR= 0.16, CI=0.03-0.46, p=0.02;I2=0%). The mean deep infection rate in the open group was 1.4% (0-5%) while no deep infection was reported in MIS, with no statistically significant difference (RR= 3.24, CI=0.48-20.54, p= 0.23;I2=0%). The mean superficial infection rate was 6.04% (0-18.2%) and 0.40% (0-4.5%) for open and MIS repairs, respectively, with statistically significant difference (RR= 5.70, CI=1.80-18.02, p< 0.001;I2=0%). Conclusion: Open Achilles tendon repair is associated with longer surgical time, higher risk of superficial infection, and ankle stiffness, while MIS repair is associated with a greater risk of temporary sural nerve palsy. Re-rupture rate and functional outcomes are mostly equivalent. We found MIS to be a safe and reliable technique. However, high-quality standardized RCTs are still needed before recommending MIS as the gold standard for the management of Achilles tendon rupture.